Electrodeposited silver amalgam particles on pyrolytic graphite in (spectro)electrochemical detection of 4-nitrophenol, DNA and green fluorescent protein - Sebest, Peter; Fojt, Lukas; Ostatna, Veronika; Fojta, Miroslav; Danhel, Ales (Bioelectrochemistry, 2020)
Catalytic properties and high adsorption affinity of nucleic acids and proteins to silver amalgam electrode surface make this kind of electrified interface perspective for bioanalytical and biomedical applications. For the first time, a basal-plane pyrolytic graphite electrode (bPGE) has been used as a substrate for electrodeposition of silver amalgam particles (AgAPs). Optimization of the resulting composition, surface morphology and electrochemical properties of the AgAPs was done by scanning electron microscopy with energy disperse X-ray spectroscopy, image processing software and voltammetric detection of electrochemically reducible model organic nitro compound, 4-nitrophenol. Spectro-electrochemical applicability of bPGE-AgAP has been demonstrated by electrolysis of 4-nitrophenol. Simultaneous UV-Vis-chronoamperometry provided information on the number of exchange electrons and the reduction rate constants. Preferential adsorption of the fluorescently labelled calf thymus DNA and the green fluorescent protein (GFP) on the surface of AgAPs was observed by fluorescence microscopy. In contrast to previously studied indium-tin oxide and vapour-deposited gold decorated by AgAPs, herein the presented bPGE-AgAP has provided sufficiently wide negative potential window allowing direct electroanalysis of non-labelled DNA and GFP using intrinsic electrochemical signals independently of the fluorescent labelling. The bPGE-AgAP can thus be expected to find application opportunities in protein electrochemistry, (bio)sensor development or in-situ spectro-electrochemical studies.
Keywords: elektrochemické techniky; Adsorption; Electrochemical Techniques; Silver; nitrofenoly; zelené fluorescenční proteiny; Green Fluorescent Proteins; DNA; mikroskopie elektronová rastrovací; Electroplating; Nitrophenols; pokovování galvanické; stříbro; adsorpce; Microscopy, Electron, Scanning